2016
DOI: 10.1002/14651858.cd002787.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide for acute respiratory distress syndrome (ARDS) in children and adults

Abstract: GRADE Working Group grades of evidence High quality: Further research is very unlikely to change our confidence in the estimate of effect Moderate quality: Further research is likely to have an important impact on our confidence in the estimate of effect and may change the estimate Low quality: Further research is very likely to have an important impact on our confidence in the estimate of effect and is likely to change the estimate Very low quality: We are very uncertain about the estimate a Sensitivity analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
0
15

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(205 citation statements)
references
References 82 publications
5
170
0
15
Order By: Relevance
“…Subsequent studies showed similar improvements in oxygenation in a dosedependent manner without better outcomes [10]. Multiple systematic reviews have shown that iNO does not reduce the mortality among patients with ARDS, nor does it shorten the duration of mechanical ventilation and it may even increase the incidence of renal impairment [9]. Nevertheless, one study showed that low iNO doses (< 5 ppm) improved lung function in ARDS survivors at 6 months [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies showed similar improvements in oxygenation in a dosedependent manner without better outcomes [10]. Multiple systematic reviews have shown that iNO does not reduce the mortality among patients with ARDS, nor does it shorten the duration of mechanical ventilation and it may even increase the incidence of renal impairment [9]. Nevertheless, one study showed that low iNO doses (< 5 ppm) improved lung function in ARDS survivors at 6 months [15].…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled nitric oxide (iNO) is a selective pulmonary vasodilator that has long been used in the management of acute respiratory distress syndrome (ARDS), pulmonary hypertension, neonatal hypoxemic respiratory failure, and lung transplantations. To date, several randomized controlled trials and meta-analyses have concluded that iNO therapy wasn't beneficial to mortality or mechanical ventilation duration of patients with ARDS [9,10]. However, postoperative hypoxemia in AADA was different with ARDS in etiology and pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…However, NO gas has been advocated as rescue treatment in adults with hypoxic ARDS [8]. Treatment with iNO reversed pulmonary hypertension, improved remarkably severe hypoxemia and shortened the length of ventilatory support as compared to matched control patients with SARS-CoV [9].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…We agree with Li et al that this is an alarming trend given the proven efficacy and cost effectiveness of PP compared to ECMO. Other rescue therapies, such as inhaled nitric oxide, have been found to improve gas exchange, but have not offered survival benefit in ARDS; therefore, they are also poor alternatives to PP (25). Unfortunately, there remains no proven pharmacologic therapy in the treatment of ARDS, but research in this area is ongoing.…”
Section: Alternatives To Pronementioning
confidence: 99%